Metal–organic frameworks with 5, 5′-(1, 4-xylylenediamino) diisophthalic acid and various nitrogen-containing ligands for selectively sensing Fe(iii)/Cr(vi) and nitroaromatic compounds. Issue 14 (6th March 2019) - Xu, Cungang; Bi, Caifeng; Zhu, Zheng; Luo, Rong; Zhang, Xia; Zhang, Dongmei; Fan, Chuanbin; Cui, Liansheng; Fan, Yuhua
Abstract : Four Zn(ii ) complexes are applied in selectively sensing Fe(iii )/Cr(vi ) and nitroaromatic compounds. Abstract : Four novel Zn(ii ) metal–organic frameworks (MOFs) including [Zn(L)0.5 (bimb)]·2H2 O·0.5(CH3 )2 NH n (1 ), [Zn(L)0.5 (bimmb)]·2H2 O n (2 ), [Zn(L)0.5 (btdpe)]·H2 O n (3 ), and [Zn(L)0.5 (bidpe)] n (4 ) (H4 L = 5, 5′-(1, 4-xylylenediamino) diisophthalic acid, bimb = 1, 4-bis(imidazol-1-yl)-butane, bimmb = 1, 4-bis(imidazol-1-ylmethyl)benzene, btdpe = 4, 4′-bis(4 H -1, 2, 4-triazol-4-yl)diphenyl ether, and bidpe = 4, 4′-bis(imidazolyl)diphenyl ether) were solvothermally prepared and further characterized by elemental analysis, IR spectroscopy, single-crystal X-ray diffraction, thermogravimetric (TG) analysis and powder X-ray diffraction (PXRD). Single-crystal X-ray diffraction analysis showed that complex1 features a 3-fold interpenetratedbbf topological framework with the Schläfli symbol of (6 4 ·8 2 )(6 6 )2 . Complex2 displayed an unprecedented 2-nodal (4, 4)-connected 3D framework with the Schläfli symbol of (8 6 ), while complexes3 and4 showed 3-nodal (2, 4, 4)-connected (4·8·10 4 )2 (4)2 (8 4 ·10·12)-unprecedented frameworks. Luminescence studies revealed that complexes1–4 can be used as high selectivity luminescence sensors for sensing Fe(iii ) cations, Cr(vi ) anions (Cr2 O7 2− and CrO4 2− ) and nitroaromatic compounds. Furthermore, a possible sensing mechanism was investigated in this paper.